Data supporting: 'Quick coherence technique facilitating commercial pilots' psychophysiological resilience to the impact of COVID-19' - Li, Wenliang; Zhang, Jingyi; Braithwaite, Graham; Kearney, Peter (Cranfield University, 2022)
Eighteen commercial pilots voluntarily participated in a two-day training on quick coherence technique (QCT) following a two-month self-regulated practicing QCT during the controlled rest breaks in the flight deck and day-to day life. There are subjective and objective assessments to evaluate the effects on QCT biofeedback.
Keywords: aviation safety; resilience (psychology); biofeedback (psychology)